A route for a strong increase of critical current in nanostrained iron-based superconductors - Toshinori Ozaki (Nature Portfolio, 2016)
Simultaneous increase of critical temperature and critical current in superconductors is desirable for application purpose, but very difficult to realize. Here, Ozaki et al. report a simultaneous enhancement of Tc and Jc in FeSe0.5Te0.5films with cascade defects produced by low-energy proton irradiation.